2009
DOI: 10.1606/1044-3894.3868
|View full text |Cite
|
Sign up to set email alerts
|

Getting Out: Factors that Influenced Abused Wives’ Decisions to Leave Their Abusive Spousal Relationships in Singapore

Abstract: Abused wives who left their abusive relationships help us to understand the factors that enabled them to decide on leaving. This article reports the decision-making phase (as part of a larger study) through the experiences of two ethnic Chinese, one Indian Muslim, and five Malay Muslim women in Singapore. Using an ecological perspective, the study found the urgency of their abusive situation and a change in awareness regarding the impact of the abuse on their children and themselves were the main factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For this reason, they advocated using the ecological model of social work to address the integration of domestic and family violence screening programs into healthcare settings (Thurston & Eisener, 2006). Other researchers have also used the ecological framework for addressing domestic and family violence and gendered violence (Carlson, 1997;Casey & Lindhorst, 2009;Khng & Ow, 2009;Powell, 2011;VicHealth, 2010) as it is particularly useful to focus on sustainable, not short-term change, to recognise complexity and to explore transactions both within and across systems (Healy, 2005). Child psychologist, Urie Bronfenbrenner (1979) further developed the ecological model, identifying micro (individual), meso (organisations, services, and collectives) and macro level (social policies, laws, and social institutions) environmental factors.…”
Section: The Screening Programmentioning
confidence: 99%
“…For this reason, they advocated using the ecological model of social work to address the integration of domestic and family violence screening programs into healthcare settings (Thurston & Eisener, 2006). Other researchers have also used the ecological framework for addressing domestic and family violence and gendered violence (Carlson, 1997;Casey & Lindhorst, 2009;Khng & Ow, 2009;Powell, 2011;VicHealth, 2010) as it is particularly useful to focus on sustainable, not short-term change, to recognise complexity and to explore transactions both within and across systems (Healy, 2005). Child psychologist, Urie Bronfenbrenner (1979) further developed the ecological model, identifying micro (individual), meso (organisations, services, and collectives) and macro level (social policies, laws, and social institutions) environmental factors.…”
Section: The Screening Programmentioning
confidence: 99%
“…For victims of IPV, concern for the safety and well-being of children is often a primary motivation for seeking help (Burgess-Proctor, 2008;Kelly, 2009;Khng & Ow, 2009;Petersen, Moracco, Goldstein, & Clark, 2005;Ptacek, 1999;Taylor, 2002). Therefore, the role that children play in women's service utilization and decisionmaking processes is an important area of empirical research (Khaw & Hardesty, 2007).…”
mentioning
confidence: 99%
“…Khng and Ow (2009) explored factors that influenced women’s decision-making in their process of leaving abusive relationships in Singapore, engaging Muslim, Roman Catholic, and Buddhist believers. The study found that religious faith had an important influence on the women’s process of leaving.…”
Section: Resultsmentioning
confidence: 99%